2018
DOI: 10.1111/imm.13003
|View full text |Cite
|
Sign up to set email alerts
|

Screening the full leucocyte receptor complex genomic region revealed associations with pemphigus that might be explained by gene regulation

Abstract: Pemphigus foliaceus (PF) is a blistering autoimmune skin disease rare in most of the world but endemic in certain regions of Brazil. PF is characterized by the detachment of epidermal cells and the presence of autoantibodies against desmoglein 1. In previous studies, we have shown that genetic polymorphisms and variable expression levels of certain leucocyte receptor complex (LRC) genes were associated with PF. However, the role of the LRC on PF susceptibility remained to be investigated. Here, we analysed 527… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The Journal of Immunology autoimmune thyroiditis (6)(7)(8)(9)(10)(11)(12)(13). Mounting evidence also supports the immune checkpoint function of LILRB1 in viral chronic infection and cancer (76)(77)(78).…”
Section: Discussionmentioning
confidence: 89%
“…The Journal of Immunology autoimmune thyroiditis (6)(7)(8)(9)(10)(11)(12)(13). Mounting evidence also supports the immune checkpoint function of LILRB1 in viral chronic infection and cancer (76)(77)(78).…”
Section: Discussionmentioning
confidence: 89%
“…Collagen in tumor matrix and damaged tissues is a common ligand for LAIR1 in broad spectrum, inhibiting immune cell functions after ligation, while LAIR2 was found to be a soluble protein with similar extracellular domain, which could block LAIR1 binding by competing ligands (55)(56)(57)(58). Former studies also showed in autoimmune diseases, expression of LAIR2 was increased, and genetic single nucleotide polymorphism of LAIR2 was related to susceptibility of autoimmune diseases (59)(60)(61)(62). The knowledge of LAIR2 in TIME regulation is limited, however, LAIR2 could interfere platelet activation and adhesion, and secreted LAIR2 could inhibit classical and lectin pathways of complement system in killing pathogens (58,63).…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide expression profiling with approximately 55,000 probes revealed that several genes in 19q13 were differentially expressed in CD4+ lymphocytes when comparing FS patients and controls, as well as between different FS clinical forms ( Malheiros et al , 2014 ). Motivated by this result, recently the whole 1.5 Mb LRC was screened in a case-control study using genotype data of 527 tag SNPs of which three were associated with differential susceptibility to FS ( Farias et al , 2019 ). The intergenic SNP rs465169 is in a region that regulates several immune-related genes, including VSTM1, LAIR1, LILRA3-6, LILRB2, NLRP12, and LENG8.…”
Section: Pemphigus Geneticsmentioning
confidence: 99%